FAKTIR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK BERKARIR DI BIDANG PERPAJAKAN - Shintya Khairunnisa; Rahmat Kurniawan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
The purpose of this study is to examine the factors that influence students of accounting study program to choose a career in taxation. The Theory of Reasoned Action and Theory of Planned Behavior model is integrated with the four factors that used in this study, perceptions toward taxation profession, social guidance, self efficacy, and expectations toward the career in taxation. Data were collected by quistionnaire,obtainning 120 sample. Using multiple linear regression method, this study finds that social guidance factor and expectations toward the career in taxation are significantly influence the student’s intention to choose the career in taxation field. Findings of this study convey the practical implication to the accounting departement to explain more, and give a good impression about the proffession in taxation field